1994
DOI: 10.1007/bf00023243
|View full text |Cite
|
Sign up to set email alerts
|

Molecular features, processing and import of the Rieske iron-sulfur protein from potato mitochondria

Abstract: The mitochondrial iron-sulfur protein (also termed Rieske iron-sulfur protein) of cytochrome c reductase was purified from potato tubers and identified with heterologous antibodies. The sequences of the N-terminus of this 25 kDa protein and of an internal peptide were determined to design oligonucleotide mixtures for screening a cDNA library. One class of cDNA clones containing an open reading frame of 265 amino acids was isolated. The encoded protein contains the peptide sequences of the 25 kDa protein and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…A spot containing the mature form of the mitochondrial Rieske Fe-S protein, a component of the mitochondrial cytochrome bc 1 complex (Emmermann et al, 1994), increased after all bacterial challenges. Remarkably, this spot was not present in the mock MgCl 2 treatment, suggesting that this represents a rapid and highly specific mitochondrial PAMP response.…”
Section: Pamp-responsive Proteins-mitochondriamentioning
confidence: 99%
“…A spot containing the mature form of the mitochondrial Rieske Fe-S protein, a component of the mitochondrial cytochrome bc 1 complex (Emmermann et al, 1994), increased after all bacterial challenges. Remarkably, this spot was not present in the mock MgCl 2 treatment, suggesting that this represents a rapid and highly specific mitochondrial PAMP response.…”
Section: Pamp-responsive Proteins-mitochondriamentioning
confidence: 99%
“…107, 1995 In plants little is known about the small subunits of the bcj complex. Cyt c reductase from potato (Solanum tuberosum) comprises 10 subunits (Berry et al, 1991;Braun and Schmitz, 1992;Braun et al, 1994) and was shown to include the activity of the general mitochondrial processing peptidase, which cleaves off the presequences of nuclear-encoded mitochondrial precursors upon their import into the organelle (Braun et al, 1992a(Braun et al, , 1994. Here we report the identification, topography, sequence, and import pathway of the 14-kD protein from higher plants.…”
mentioning
confidence: 79%
“…Antibodies were raised against the 14-kD protein from potato and used for immunological identification of the corresponding subunits of Cyt c reductase from wheat. The proteolytic fragmentation of the 14-kD proteins from potato and wheat, the separation of the generated peptides by reverse-phase HPLC, and the N-terminal sequencing of peptides by cyclic Edman degradation are described elsewhere (Braun et al, 1994).…”
Section: Purification and Analysis Of Cyt C Reductase From Potato Andmentioning
confidence: 99%
See 2 more Smart Citations